2017
DOI: 10.1093/gbe/evx130
|View full text |Cite
|
Sign up to set email alerts
|

Papio Baboon Species Indicative Alu Elements

Abstract: The genus of Papio (baboon) has six recognized species separated into Northern and Southern clades, each comprised of three species distributed across the African continent. Geographic origin and phenotypic variants such as coat color and body size have commonly been used to identify different species. The existence of multiple hybrid zones, both ancient and current, have complicated efforts to characterize the phylogeny of Papio baboons. More recently, mitochondrial DNA (mtDNA) and Y-chromosome genetic marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In Preparation). Recent work also supports that the expansion of Alu elements is not unique to the olive baboon, but rather the Papio lineage as a whole [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In Preparation). Recent work also supports that the expansion of Alu elements is not unique to the olive baboon, but rather the Papio lineage as a whole [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 89%
“…The recent findings of the Baboon Genome Analysis Consortium, along with other recent studies of mobile elements in the baboon genome have provided a great deal of new information (Rogers et al: The comparative genomics, epigenomics and complex population history of Papio baboons. In Preparation) [ 33 , 35 ]. This study found 127 novel Alu element subfamilies, supporting the high Alu mobilization rate reported by the Baboon Genome Analysis Consortium (Rogers et al: The comparative genomics, epigenomics and complex population history of Papio baboons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The less threatened African species include several remarkably flexible, ecologically generalist species like the Papio baboons (Codron, Lee‐Thorp, Sponheimer, de Ruiter, & Codron, , ; Jolly, ; Whiten, Byrne, Barton, Waterman, & Henzi, ), which adapt effectively to many anthropogenic contexts (Bergman & Kitchen, ; Hoffman & O'Riain, ; Warren, ). The genus Papio comprises six closely related taxa (Walker et al, ; Zinner, Wertheimer, Liedigk, Groeneveld, & Roos, ), usually given specific status despite a history of hybridization in contact zones (Charpentier et al, ; Jolly, Burrell, Phillips‐Conroy, Bergey, & Rogers, ; Wall et al, ; Wango et al, ). They are thought to have begun diverging approximately 2 million years ago (Zinner, Groeneveld, Keller, & Roos, ), and collectively occupy most of sub‐Saharan Africa (Winder, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considered nearly homoplasy-free [ 48 , 49 ], most potential sources of homoplasy involving Alu elements can be resolved through Sanger sequencing [ 41 , 42 , 61 ]. Recent studies demonstrate the utility of Alu elements for Papio species identification, as well as retrieving population structure within distinct Papio species [ 28 , 29 ]. Furthermore, Alu elements have been successfully used to resolve controversial relationships between primates [ 38 , 39 , 42 , 64 ].…”
Section: Introductionmentioning
confidence: 99%